MENINGKATKAN PENGETAHUAN HIPERTENSI DENGAN MENGGUNAKAN METODE EMO-DEMO - Abdillah, Alvin (STIKES NGUDIA HUSADA MADURA, 2025)
The elderly are one of the groups of people who are vulnerable to diseases because they have different physiological and psychological functions. Hypertension is one of the most dangerous health problems around the world because hypertension is a major risk factor for cardiovascular diseases such as heart attack, heart failure, stroke and kidney disease. The purpose of this community service is to apply the results of previous research, namely to increase the knowledge of the elderly on hypertension prevention with the Emo-Demo method. This community service was carried out by starting with counseling activities about hypertension and then demonstrating hypertension intervention with the Emo-Demo method, followed by measuring blood pressure and blood glucose levels. The results of the examination based on the level of hypertension were more than half of the elderly were categorized as level one hypertension 13 (38%) and level two as many as 17 elderly (50%), while based on blood glucose levels, half of them were categorized as normal as many as 17 elderly people (50%). Based on the results of the general evaluation of the intervention carried out in community service, after being evaluated, it was found that most of the elderly understood and were motivated to care about hypertension prevention with the Emo-Demo method. The next suggestion is that in order for this activity to continue, it is necessary to strengthen the posyandu cadres to continue to provide knowledge on how to prevent hypertension using the Emo-Demo method